CONFLICT MANAGEMENT STYLE IN THE WORK OF MEDICAL SPECIALISTS IN HOSPITALS - Ekaterina Raykova; Maria Semerdjieva; Biyanka Tornyova (Journal of IMAB, 2020)
Purpose: This research aims to determine the prevalent conflict management styles of medical specialists. Material and methods: By means the directindividual poll was studied the opinion of 302 medical employees at four general hospitals on the territory of the town of Plovdiv and town of Asenovgrad, Bulgaria. Of all respondents, 223 (73.8±2.53%) were healthcare specialists, and 79 (26.2±2.53%) were physicians. Thomas-Kilmann conflict instrument (TKI) was used to assess the person's predisposition to the preferred behavioural style of conflict resolution. The data were analysed using descriptive statistics. The statistical analysis was performed using SPSS v. 16. Results: In a conflict situation, preferred behavioural strategies among investigated medical professionals are compromise (7.65±0.10) and avoidance (7.44±0.11), less competing(4.01±0.13). Physicians are more likely to express collaboration and competing while healthcare professionals prefer avoidance as a strategy of behaviour in a conflict situation. Conclusions: The behaviour of medical practitioners in conflict situations has a complex determinant. This puts forth the necessity to take into account the complex conditions of the individual personal qualities, the type of working relationships, the specifics of the working environment which influence the occurrence of the conflicts in the hospital and the measures for their solution.